Analisis Semiotik Iklan Politik Prabowo Gibran Pada Pilpres 2024 - Permadi, Didi; Suparto, Diryo; Bisri, Ahmad Zaini (Universitas Djuanda Bogor, 2024)
General elections are a crucial moment in the life of the nation and state. This moment is used by political figures to build positive perceptions through political advertising. Political advertising has the main function as a strategic communication tool in the democratic process. This research aims to uncover the meaning and communication strategies used in Prabowo Gibran's political advertisements during the 2024 Presidential Election. The focus of this research is to decipher the symbolic meaning and messages contained in political advertisements using Charles Sanders Pierce's semiotic theory as a basis for exploring the signs- signs that appear in these political advertisements. By referring to Charles Sanders Pierce's semiotic theory, this research tries to identify and analyze the signs that appear in the Prabowo Gibran couple's political advertisements, both visual and verbal. Charles Sanders Pierce's semiotic analysis carried out by outlining three important components, namely Sign, Object, Interpretant, shows that political advertisements have a distinctive communication style as part of their political communication strategy. Semiotic analysis also places this advertisement in the positive category, indicating that the message conveyed is able to create meaning that supports the positive image of the couple.